Understanding social exclusion - Agulnik, Phil; Le Grand, Julian; Piachaud, David; Hills, John (Oxford University Press, 2002)
This book explores the issue of social exclusion. It asks three main questions: How can social exclusion be measured? What are its main determinants or influences? And what policies can reduce social exclusion? The authors aim to consider how a focus on social exclusion may alter the policy questions that are most relevant by fostering debate in government, research, and academic circles.
Keywords: dospělí; sociální odcizení; Poverty; Child; Social Isolation; sociální práce; dítě; sociologie; sociální izolace; Social Alienation; chudoba; Adult; Social Work